Stochastic growth with social-status concern: the existence of a unique stable distribution - Liutang Gong; Xiaojun Zhao; Yunhong Yang; Hengfu, Zou (Journal of Mathematical Economics, 2010)
This paper extends Kurz's (1968) growth model to a stochastic growth framework with social-status concern and unbounded production shocks. Using the stochastic monotonicity of a stochastic dynamic system and the methods adopted in Zhang (2007), the existence, uniqueness, and stability of invariant distribution are investigated. Different from the existence of multiple steady states under certainty, it is shown here that there exists a unique stable invariant distribution under uncertainty.